Comparison of lift velocity and power output between barbell and dumbbell bench presses - Littlefield, J. D.; Schramm, K. K.; Mayhew, J. L. (Journal of Trainology, 2021)
Objectives: The purpose of this study was to assess differences in bench press velocity and power production with barbell and dumbbells. Design: Randomized cross-over design. Methods: College men (n = 20, age = 18-24 yrs) were measured for average and peak velocities and power during maximal effort single repetitions using barbell and bilateral dumbbells at loads equivalent to 30%, 50%, and 70% of body mass. Three repetitions were performed at each load with one-minute recovery between each repetition and 10 minutes between loads. During each repetition for each mode, average and peak velocity and power were monitored using a linear accelerometer. Results: Interclass correlation coefficients across the 3 trials for peak and average velocities were high for both barbell (ICC = 0.957 and 0.821, respectively) and dumbbells (ICC = 0.947 and 0.855, respectively). Peak power output was sig nificantly higher (p < 0.009) for barbell than dumbbells at 50% and 70% loads. Average power output was significantly different (p < 0.001) across the 3 loads but not significantly different between barbell and dumbbells (p = 0.35). Although velocity decreased as load increased, higher power outputs were produced across increases in loads. Peak power output was reached at 70% of body mass with barbell and 50% with dumbbells. Conclusion: Either barbell or bilateral dumbbell bench press exercises can be used to evaluate upper-body power with sim ilar effectiveness.